Integrated photonics for quantum information science - Politi,A; Matthews,JCF; Laing,A; Peruzzo,A; Poulios,K; Meinecke,J; Bonneau,D; Shadbolt,P; Fry,D; Kalasuwan,P; Zhou,XQ; Lobino,M; et al. (2011)
New components are required to take full advantage of the integrated photonic architecture for Quantum Information science. We demonstrate quantum interference in MMI couplers and twoparticle quantum walks in coupled waveguides, showing unique quantum behaviour. FIO/ LS Technical Digest © 2011 OSA.